Perilaku Konsumen Berbelanja di Minimarket Gunung Mas Abadi Balikpapan - Nina Indriastuty; Sukimin Sukimin; Stepanus Deddy Deomedes (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
Nowadays, consumers have several alternative places to shop to meet their needs, one of them is minimarket. Minimarket becomes consumer choice because product quality and price tend to be cheaper. In addition to the minimarket, marketers can know the needs and desires of consumers, as well as directly to know what the consumer complaints. Therefore, this study was conducted with the aim to know that culture, social, personality and psychological influence consumer decisions to shop at Minimarket Gunung Mas Abadi Balikpapan, either simultaneously or partially. The analytical tool used in this research is in the form of Multiple Regression Linear. The results showed that simultaneously culture, social, personality and psychological have the significant influence on consumer decision of shopping. While the part that has a dominant influence is culture compared to social, personality and psychological, it answers the fifth hypothesis in this study.